Gene fusion involving the insulin‐like growth factor 1 receptor in an ALK‐negative inflammatory myofibroblastic tumour. Issue 7 (24th April 2019) - Piarulli, Giuseppe; Puls, Florian; Wängberg, Bo; Fagman, Henrik; Hansson, Magnus; Nilsson, Jenny; Arbajian, Elsa; Mertens, Fredrik
Abstract : Aims: Inflammatory myofibroblastic tumour (IMT) is a soft tissue tumour primarily affecting children and young adults. Approximately 50% of IMTs have gene fusions involving the receptor tyrosine kinase (RTK)‐encoding ALK gene, providing a molecular rationale for treating IMT patients with unresectable tumours with tyrosine kinase inhibitors (TKI). However, a subset of IMT instead displays fusions affecting other RTKencoding genes, so far including NTRK3, PDGFRB and ROS1 . Also, IMTs with variant RTK fusions may respond well to TKI treatment, but can be dif?cult to identify as they are negative for ALK staining at immunohistochemistry, the standard method for detection of ALK rearrangements. Materials and methods: We used RNA‐sequencing to search for alternate fusion events in an ALK‐negative IMT. Results and conclusions: We found a novel fusion gene ‐ FN1‐IGF1R. The FN1 gene, encoding ?bronectin, is thought to provide a strong promoter activity for the kinase domain of the RTK insulin‐like growth factor 1 receptor, a mechanism similar to previously described RTK fusions in IMT.